Evolution of Civil-Military Relations in Bangladesh: A Comparative Study in the Context of Developing Countries - Akkas Ahamed,; Rahman, Md. Sayedur; Nur Hossain, (Technium Social Sciences Journal, 2020)
Although Civil-military relations have historically been recognized as a subject of study in the developed world, it has become a subject of study in the region since World War II due to military intervention in newly independent Third World countries. Although the country became independent on the basis of Civil-Military relations in the war of liberation of Bangladesh in 1971, the relations did not last long. Civil-Military relations have been the subject of renewed research in Bangladesh since the establishment of the military-backed government on 1/11, 2007. The study discusses the historical context of Civil-Military relations, the nature of Civil-Military relations in Bangladesh, various activities under military rule, and political leadership. The roles of the military in the formation of the country have been analyzed. The limitations of Bangladesh's Civil-Military relations have been discussed on the basis of the experiences gained through personal interviews of high-ranking Civil-Military members and general public. In this study has been described on the civil-military relations in the light of developing countries which have been under military rule for several decades during the 1950s, 60s, 70s, 80s and 90s. Therefore in carrying out this study, the civil-military relations in other developing countries and Bangladesh have been analyzed to understand the comparative aspects of civil-military relations at both local and global level. In addition, guidelines have been given on what should be the military-civil relations in the Political System of Bangladesh.